Innovative Da'wah Practices of Abdullah Syafi'ie: Strengthening Islamic Educational Institutions in Indonesia - Choirin, Muhammad; Kamal, Fathurrahman; Iqbal, Moch. (Badan Litbang dan Diklat Kementerian Agama RI, 2024)
This study highlights the significant contributions of Abdullah Syafi'ie to Islamic education in Indonesia, particularly through his dual roles as a preacher (muballigh) and educator. The primary objective of this research is to explore how Abdullah Syafi'ie’s innovative da’wah practices have influenced and strengthened educational institutions. By employing a mixed-methods approach, this study integrates a comprehensive review of existing literature with empirical field research. The data sources include books, journals, scholarly works, and field observations, as well as interviews conducted with individuals knowledgeable about Abdullah Syafi'ie’s work. The analysis reveals Abdullah Syafi'ie's excellence in both preaching and education, highlighting his remarkable abilities in literary and managerial domains, which have played a crucial role in the establishment and development of educational institutions. His innovative approaches in integrating modern educational concepts with da’wah strategies, particularly through the use of media and strategic preaching, have led to the successful advancement of these institutions. This study offers valuable insights into the relationship between religious leadership and educational reform, demonstrating the profound impact of Abdullah Syafi'ie's contributions on the evolution of Islamic education in Indonesia. The findings have significant implications for future research and practice in the fields of da’wah and education.